(untitled) - John Locke (1632-1704) (Indiapolis, Indiana, 1983)
It is the battle for toleration and the persecution, the suffering and loss of friends, that Locke writes about in A Letter Concerning Toleration, with an intensity of moral conviction and of moral outrage unparalleled in western political theory. He now argues that toleration of religious and civil liberty is no longer a matter for debate or for the prudential judgements of the magistrate
Keywords: toleration